PEMANFAATAN MEDIA PEMBELAJARAN IPS DI SDN 2 MARGA MULYA KECAMATAN SUNGAI LOBAN KABUPATEN TANAH BUMBU - I Kadek Sugiarta (Universitas Lambung Mangkurat, 2013)
The low learning outcomes Social Studies sixth grade students of SDN 2 Marga Mulya Sungai LobanTanah Bumbu. Teachers tend to use the lecture method, less use of instructional media in teaching Social Studies. One alternative to overcome this problem is the use of Social Studies Learning Media. This study, researchers used a qualitative approach. Researchers sought to explore in order to get the data naturally or it is in the field through intensive observation and communication with the various data sources. Data collection techniques in this study, namely: (1) observation, (2) interviews, (3) documentation, (4) combined. Based on the survey results revealed (1) Media Social Studies owned learning maps, Globe, learning CD, fruit atlases, books for students 2:1, Social Studies landscape posters Kits. Teachers utilize instructional media Social Studies owned schools adapted to the material made in the RPP and make LKS. In the early observations of teachers utilize instructional media lacking Social Studies maps and completeness of the material globe.pada map. Student learning outcomes are less satisfactory completed. Observation of both teachers utilize instructional media whiteboard, maps, globes, pictures, student involvement in the use of media in the material sample countries in the continent of Asia, Learning outcomes of the students final test average 100% mastery. From the results of student responses of strongly agreed students answered happy implemented by utilizing the Social Studies learning instruction media material easier to understand because it is done with real world example so that they can know the matery that is still abstract to concrete.Keywords: Learning Media Social Studies